Decolourisation And Cod Reduction Of Methylene Blue And Dye Wastewater Using Sphingomonas Paucimobilis - Hasnam, Che Noraini Che (2013)
Microbial decolourisation and degradation is an environmentally friendly and cost competitive alternative process in the treatment of dye wastewater. In this study, the decolourisation and degradation of Methylene blue (MB) by a Sphingomonas paucimobilis strain isolated from industrial wastewater was investigated. Experimental results were assessed in terms of chemical oxygen demand (COD) reduction and decolourisation of dye wastewater using S. paucimobilis. It was found to be capable in reducing the concentration of COD at 92.99 % and achieving 85 % in decolourisation at optimal conditions of pH 9.0 and at inoculums size of 185-mL within incubation HRT of 5 days. Analysis of samples extracted from decolourised culture flasks at pH 9.0 using Fourier transform infrared (FTIR) spectroscopy confirmed that the mechanism of colour removal was due to biodegradation. In addition, scanning and transmission electron microscopy revealed the secretion of exopolysaccharides (EPS) by S. paucimobilis cells on exposure to dye that showed a probable physiological defence mechanism to ensure controlled diffusion of dye molecules into cellular structures. The experiment were performed under steady state conditions to determine the kinetic coefficients such as growth yield (Y), specific biomass decay (Kd), maximum specific substrate utilisation (K), saturation constant for substrate (Ks), maximum specific biomass growth rate (μmax), and critical retention time (θc). The kinetic coefficients were evaluated using Monod equation. The bio-kinetic coefficients Y, Kd, k, Ks, and μmaxwere found to be 1.879, 0.013 per day, 0.540 per day, 4214.7 mg/L and 1.015 per day, respectively.